Diagnostic Performance of Diffusion-Weighted Imaging for Colorectal Cancer Detection: An Updated Systematic Review and Meta-Analysis - Xiao, Yunfei; Li, Juan; Zhong, Jiamei; Chen, Dequan; Shi, Jianbo; Jin, Hongrui (Frontiers in Oncology, 2022)
Background: Magnetic resonance imaging (MRI), which use strong magnetic fields and radio waves (radiofrequency energy) to make images, is one of the best imaging methods for soft tissues and can clearly display the unique anatomical structures. Diffusion-weighted imaging (DWI) has been developed for identifying various malignant tumors. Aim: To investigate the diagnostic value of DWI magnetic resonance imaging (MRI) quantitative analysis in colorectal cancer detection. Methods: The PubMed, Cochrane library, and Embase databases was searched from inception to May 29, 2020. Studies published in English that used DWI-MRI for diagnosing colorectal cancer were included. Case reports, letters, reviews, and studies conducted in non-humans or in vitro experiments were excluded. The pooled diagnostic odds ratio (DOR) and hierarchical summary receiver operating characteristic (HSROC) curves were computed for DWI, and the area-under-the-curve (AUC) and associated standard error (SE) and 95% confidence intervals (CIs) were also used. Results: In total, 15 studies with 1655 participants were finally included in this meta-analysis. Four prospective studies and eleven retrospective studies. Eight studies focused on rectal cancer, six on colorectal cancer, and one on colonic cancer. The performance of DWI-MRI for diagnosing colorectal cancer was accurate, with pooled sensitivity, specificity, and positive likelihood ratio, negative likelihood ratio of 0.88 (95% CI = 0.85-0.91), 0.92 (95% CI = 0.91-0.94), 30.36 (95% CI = 11.05-83.43), and 0.44 (95% CI = 0.30-0.64), respectively. The pooled diagnostic odds ratio (DOR) and hierarchical summary receiver operating characteristic (HSROC) curves were 121 (95% CI = 56-261) and 0.92 (λ: 4.79), respectively. Conclusion: DWI showed high diagnostic accuracy for colorectal cancer detection. Further studies with large sample sizes and prospective design are needed to confirm these results.